Examining the Effects of NHIS Claims Reimbursement on Financial Sustainability of Service Providers - M. Dubik, Niibman; Anankpieng, Benjamin Aseira; Abdul Razak, Abubakari (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This study used a cross-section survey and descriptive design with a quantitative approach to examine the factors influencing NHIS claims payment to service providers and interpret the relationship between variables. Data was collected from 161 respondents using a self-designed questionnaire. Claims reimbursement was significantly affected by claims submission, rejected claims returned, resubmission of corrected claims, part-payment of claims submitted, appeal to adjudication committee, and MOH intervention. Pearson’s correlation level shows a positive but weak correlation between independent and dependent variables at CI of 95% and 99% (p<0.05 and p<0.01) respectively. In the regression analysis, R-squared was found to be 0.273 indicating that independent variables including submission of processed claims for payment; rejection of erroneous and fraudulent claims; resubmission of corrected claims; submission of claims following NHIA directives; part-payment of submitted claims; appeal to the Adjudicating committee, and minister of health intervention influence NHIS payment of claims at 27%. However, when independent variables are kept constant at zero, payment of claims will be 0.784(78.4%). The mean of VIF of all the variables is 1.298 and that of the tolerance is 0.776. Regulatory and policy enforcement and effective stakeholder collaboration are essential to improve adherence to the operational standard guidelines of the scheme. These will safeguard the NHIS against abuses, fraud, leakages, and maleficence while improving prompt payment of service providers' claims for efficient health care delivery.